Towards a gene therapy for RP10 retinitis pigmentosa - Tam, Lawrence Chi Shing (Trinity College (Dublin, Ireland). Department of Genetics, 2008)
The main focus of this thesis is on the development of a gene therapy strategy using RNAi-mediated suppression for the RP10 form of retinitis pigmentosa (RP), which accounts for approximately 2% of all autosomal dominant RP cases. Comparative analysis of the transcriptional profiles within the retinas of mice carrying a targeted disruption of the rhodopsin gene resulted in the identification of the gene encoding inosine 5'-monophosphate dehydrogenase 1 (IMPDH1) as a candidate for RP10 (Kennan et al, 2002). IMPDH1 is the rate-limiting enzyme in the de novo biosynthesis pathway for guanine nucleotides, which are important prerequisites for many cellular functions and play crucial regulatory roles in the phototransduction cascade. Several studies have revealed that specific mutations within the IMPDH1 gene segregate with RP-affected families (Bowne et al., 2002). Furthermore, structural protein analyses have indicated that mutant IMPDH1 protein misfolding and aggregation are the likely cause of severe retinopathy in humans (Aherne et al., 2004). In contrast, IPHD1 -/- mice at four months of age, show little structural or functional degeneration of the retina (Aherne et al., 2004). This observation suggests that the dominant segregation pattern associated with RP10 is not caused by haploinsufficiency of the normal IMPDH1 gene, but that the disease pathology is caused by a dominant negative phenotypic effect exerted by mutant protein. The mild phenotype observed in IMPDH1 knockout mice has presented the human form of RP10 as a potential therapeutic target, whereby, simultaneous ablation of wild type and mutant IMPDH1 transcripts by RNA interference (RNAi), may be sufficient to abolish the dominant negative effect exerted by mutant IMPDH1 protein.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin